Ectopic molar pregnancy, rare entity: new case report - Kamal, El Harcha; Soukaina, Auragh; Hafsa, Taheri; Hanane, Saadi; Ahmed, Mimouni (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
We report in this work the case of a 24-year-old patient who was admitted to the emergency room with an acute abdomen, the investigations were in favor of a ruptured EP, the patient underwent a salpingectomy the same day due to the state of the tube, the anatomopathological study of the product was in favor of an ectopic GTD, the patient benefited from a monitoring of the levels of BCHG according to the recommended protocols, we discussed through this case the different clinical and therapeutic aspects of this rare entity.